Analysis of Quran Reading Ability Among Students of Islamic Elementary School in West Bandung Regency: Analisis Kemampuan Membaca Al-Qur'an Siswa Madrasah Ibtidaiyah Negeri di Kabupaten Bandung Barat - Al Ayyubi, Ibnu Imam; Muhammad, Fikri Rizkia; Indrawan, Deni; Nurhikmah; Rahmawati, Siti (UIN Raden Mas Said Surakarta, 2025)
This study analyzes the Quran reading ability of fifth-grade students from Islamic and public elementary schools in West Bandung Regency. A total of 104 students participated, including 33 from MI Ar-Ridhwan, 15 from MI Darussyifa Al-Musri' 1, 26 from SD Karangtanjung 2, and 30 from SD Pasir Banteng. Using a quantitative ex post facto design, the study examined the effects of school type and gender on Quran reading ability without direct intervention. The sample was selected through cluster probability sampling to ensure representation. Data were analyzed using descriptive and inferential statistics, including Two-Way ANOVA. Results showed a significant difference in Quran reading ability between students in Islamic and public schools, with MI students performing better. However, no significant gender-based differences were found. The findings highlight the impact of school context on religious learning outcomes, suggesting that the MI curriculum and pedagogy more effectively support Quran literacy. The study contributes to educational theory and underscores the need for enhanced Quran instruction in public schools through improved teaching methods and targeted teacher training.